Updated checklist of Azores Actinopterygii (Gnathostomata: Osteichthyes) - Luís M. D. Barcelos; José Azevedo; João Barreiros (Biodiversity Data Journal, 2021)
Since the first published comprehensive checklist of Azorean fishes - covering the whole EEZ region - several new records have been published and an updated checklist published in 2010. This new dataset covers all confirmed species of bony fish for the Azorean EEZ.In this update we made corrections to the previous checklists, updated the taxonomy according to the most recent bibliography and added two new species to the Azorean Actinopterygii checklist.